Value estimation of the company Metrostav a.s. - Černý, Matěj; Kislingerová, Eva, 1950-; Kolářová, Blanka; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2009)
The aim of the diploma thesis is to determine the market value of the company Metrostav a.s. to the date 1.1.2009. Final market value represents the potential market price for which the owners could sell this company to the date of evaluation. The diploma thesis starts with brief introduction of the company. Afterwards strategic analysis follows which is focused on analysis of profit potential and its result is the prediction of sales in the near future. In financial analysis are examined the financial conditions of the company on the basis of absolute, ratio and global indicators. Financial plan is based on the prediction of sales, which was estimated within strategic analysis. The company is evaluated using two-phase discounted cash flow method in the version of FCFF. The diploma thesis is ended by risk analysis of assessment value of company by using software program Crystal Ball.
Vedoucí práce: Eva Kislingerová
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2010
Rok obhajoby 2010
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses